PROFILE OF NECK STRUCTURE INJURY PATTERNS IN CASES OF HANGING – AN AUTOPSY BASED STUDY - Roy, Kallol; Panja, Saumabrata; Debnath, Bhaskar Jyoti; Khan, Joydeep (Journal of Forensic Medicine and Toxicology, 2024)
Hanging as a means to commit suicide is one of the most common methods known to mankind. But also, a common method to fabricate a murder. However, antemortem features at times are confirmatory but also confusing. This study aimed to establish the patterns of injuries to the neck structure in hanging cases. There were 228 cases of deaths caused by hanging. Hanging was most frequently reported in the 11-20 age group, comprising 30.22% (69 cases) out of 228 hanging deaths. Least seen among age group 81-90 i.e., 02 (0.87%). Above the age of 90, no deaths due to hanging were observed. Out of 228 deaths, 97 (42%) were females and 131 (57%) were males. Position of the knot was assessed, in 67 (29.3%) cases knots were on the left side of the neck, in 72 (31.5%) cases knots were on the back of the neck, in 75 (32.8%) cases knots were on right side of the neck and in 14 (6.14%) cases knots were found below the chin. Amongst all neck structure injuries, rupture/contusion of sternocleidomastoid and other strap muscles of the neck were found in 26.75% of cases. In 27.63% of cases, a carotid intimal tear was identified. Additionally, a hyoid bone fracture was observed in 1.75% of cases, and a thyroid cartilage fracture was present in 0.87% of cases. No injury to the cervical vertebra or cricoid cartilage was found.
Keywords: Hanging; Asphyxia; Neck structure injury; Ligature mark; Profile